Tinjauan Yuridis Kompetensi Absolut Pengadilan Sebagai Faktor Penyebab Tidak Dapat Diterimannnya Gugatan (Studi Kasus Putusan No 150/Pdt.G/2016/PN Lbp) - Dejan Gumelar Raja Guk-Guk; Utary Maharany Barus; Muazzul Muazzul (Universitas Medan Area, 2019)
Every party who wishes to file a lawsuit must have sufficient legal interest. To overcome the deficiencies faced by justice seekers in fighting for their interests, Article 119 HIR / Article 143 RBG authorizes the Chair of the District Court (PN) to advise and assist the plaintiffs in filing their claims. This type of research is normative juridical namely a research that deductively begins the analysis of the articles in the legislation governing the problem. The legal provisions are that the Lubuk Pakam District Court in this case is to resolve inheritance disputes over land disputes which incidentally become the Absolute Competence of the Religious Court, because it is very caseistic of a case which will later be entered and examined by a Judge. Legal protection there are parties to a dispute related to the non-receipt of a lawsuit due to absolute competence in court that legal protection there are parties to a dispute related to the non-receipt of a lawsuit due to absolute competence in court equally as getting legal protection means that both parties receive equal treatment by the court.